Adaptation of bergen shopping addiction scale to the compulsive online shopping behavior - Bozdağ, Yasemin; Yalçınkaya Alkar, Özden (Journal of Dependence, 2018)
Objective: The purpose of this study is to translate online shopping addiction version of the Bergen Shopping Addiction (BSAS) Scale, Compulsive Online Shopping Scale (KÇSA) into Turkish and determine the reliability and validity of it. Material and Methods: Scale was developed to be used for online shopping and involves 28 items. For this study, a total of 272 participants from 52 cities in Turkey, 71.3 % of which are women (n = 194), 28.7 % of which are males (n = 78), took part in the study. In addition to internet addiction measure, impulsivity, materialism, loneliness, life satisfaction, depression-anxiety and stress measures were included in the study. Results: The Cronbach Alpha internal consistency coefficient of the developed scale was found to be .95. In order to reveal the validity of the structure of the scale, the exploratory factor analysis was used, the factor structure was tested and it is seen that the scale has a 5-factor structure. The factors were called as problem-conflict-relapse, salience, mood modification, withdraw and tolerance. It was seen that the developed model was similar with the original one. Additionally as a result of the correlation analysis, there was a positive correlastion between KÇSA and internet addiction and materialism. Conclusion: KÇSA was a valid and reliable instrument for internet shopping addiction in our country...